Size management by European private firms to minimize proprietary costs of disclosure - Bernard, Darren; Burgstahler, David; Kaya, Devrimi (Journal of Accounting and Economics, 2018)
We examine size management by European private firms for which disclosure requirements increase at size thresholds. Our estimates suggest at least 8% of firms near thresholds that impose income statement disclosure manage size downward, and the average firm that manages size sacrifices more than 6% of its assets. We find that multiple determinants of proprietary costs predict this behavior, and that size management to avoid mandatory audits, which are similarly imposed at size thresholds, is of comparable magnitude. Our results triangulate the economic significance of proprietary costs in a setting largely without confounding capital market, agency, or compliance costs.